Implementation of Cooperative Learning Model Type of TPS Based SAVI to Complete Student Learning Outcome of X-Grade Students on The Material of Electrolyte and Nonelectrolyte Solution in SMAN 1 Sidoarjo (UNESA Journal of Chemical Education, 2018)
The aims of this research were to determine the learning implementation, student activity, and student learning outcome mastery after the implementation of cooperative learning model type of TPS based SAVI on the material of electrolyte and nonelectrolyte solution. The type of this research was pre-experiment research with the research design that has been used was "one group pretest-posttest design". The subjects of this research were students of X-IPA 1 SMAN 1 Sidoarjo academic year of 2017-2018 which amounted to 36 students. The results of this research indicated that there was a very good collaboration between cooperative learning type of TPS with SAVI approach. The implementation of cooperative learning model type of TPS based SAVI got average quality on the first meeting of 3.14 (very good) and the second meeting of 3.73 (very good). Students had activity time percentage of TPS and SAVI were dominant. The learning outcomes of all students on electrolyte and nonelectrolyte solution reached the individual mastery of 94.4% in the first meeting, while in the second meeting reached the individual mastery of 97.2%. This means the students of X-IPA 1 have achieved classical mastery. The conclusion of this research was cooperative learning type of TPS based SAVI can complete student learning outcome on electrolyte and nonelectrolyte solution.